Modernizing Education through Methods of Digital Transformation: New Approaches in Teaching Foreign Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the significance and role of digital transformation methods in modern education, specifically in foreign language teaching. The study analyzes the implementation of digital technologies in language teaching processes, innovative approaches, and their effectiveness. The paper discusses the role of distance learning platforms, mobile applications, and artificial intelligence technologies in language learning processes.